PENGGUNAAN PENDEKATAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPS DI KELAS IV SDN 21 BATANG ANAI KABUPATEN PADANG PARIAMAN - Yulizarni Yulizarni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
This research was that aims to improve the learning outcomes of social educatio using the approach problemsolving in class IV SDN 21 Batang Anai. The approach used a qualitative and quantitative .Subjek of research were teacher and students in class IV SDN 21 Batang Anai with 23 students.This research did in SDN 21 Batang Anai Kab.Padang Pariaman The first cyele was 66,95% increase to 81,30% in the second cyecle.Thus, approach problem solvingcan improve the learning outcomes of social education in class IV SDN 21 Batang Anai Kab. Padang Pariaman.